2019
DOI: 10.1371/journal.pbio.3000457
|View full text |Cite
|
Sign up to set email alerts
|

Cell confinement reveals a branched-actin independent circuit for neutrophil polarity

Abstract: Migratory cells use distinct motility modes to navigate different microenvironments, but it is unclear whether these modes rely on the same core set of polarity components. To investigate this, we disrupted actin-related protein 2/3 (Arp2/3) and the WASP-family verprolin homologous protein (WAVE) complex, which assemble branched actin networks that are essential for neutrophil polarity and motility in standard adherent conditions. Surprisingly, confinement rescues polarity and movement of neutrophils lacking t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 85 publications
1
78
0
Order By: Relevance
“…Similar arguments were given related to the budding of the virions from the membrane; it was suggested that membrane protein dimerization was crucial for formation of the virion membrane [39]. Re-formation of membrane constituents within the budding and vesiculation process includes conformational changes of the molecules, changes of the conditions in the adjacent solution [40] and ATP-dependent mechanisms recently recognized as active forces [41,42]. Co-operative interactions between clathrin and endocytic proteins were suggested to be involved in formation of clathrin-coated vesicles [43].…”
Section: Direct Interactions Between Membrane Constituents As a Base mentioning
confidence: 69%
“…Similar arguments were given related to the budding of the virions from the membrane; it was suggested that membrane protein dimerization was crucial for formation of the virion membrane [39]. Re-formation of membrane constituents within the budding and vesiculation process includes conformational changes of the molecules, changes of the conditions in the adjacent solution [40] and ATP-dependent mechanisms recently recognized as active forces [41,42]. Co-operative interactions between clathrin and endocytic proteins were suggested to be involved in formation of clathrin-coated vesicles [43].…”
Section: Direct Interactions Between Membrane Constituents As a Base mentioning
confidence: 69%
“…S3 D and Movie S1 ). We quantified the polarization of these proteins as performed in a recent study ( 37 ), using an approach considering angular distribution of the fluorescent signal with respect to the center of mass of the cell and the center of mass of the fluorescent signal ( Materials and Methods ). This quantification shows that following the initial formation of actin brushes at the new front (time 0) an increase in the polarity index of the back markers is observed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that expression of Arp3 was essential for cell division or perhaps cytokinesis. Indeed, Arp2/3 complex function has previously been linked to proper cell division and mitotic spindle formation (Plessner et al, 2019 ), perhaps through actin-dependent tuning of centrosomal microtubule nucleation (Farina et al, 2019 ), although it is already clear that Arp2/3 complex cannot be obligatory for cell division in all cell types and conditions (Graziano et al, 2019 ). Here we found that induced, acute Arp3 removal in fibroblasts causes dramatic increase in average centrosome numbers from roughly 2 to >5 on average in interphase cells ( Figures 10A–C , Supplementary Figures 15, 16 ).…”
Section: Resultsmentioning
confidence: 99%